Assessment of heavy metal pollution in Istanbul using plant (Celtis australis L.) and soil assays - YARCI, CELAL; ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS LTD, 2017)
In this study, plant (leaf, branch and bark) and soil samples of nettle tree were collected from 40 different localities in Istanbul, Turkey, to investigate the heavy metal pollution levels as well as to understand the employability of this plant species in pollution monitoring. Besides, the importance of pollution sources and their distance to the plant species were emphasized, and assessment of the air and soil related contamination was performed. The heavy metal concentrations in the samples were measured using atomic absorption spectrophotometry. The average highest values of Pb (14.90 +/- 2.96 mu g/g), Cd (0.65 +/- 0.13 mu g/g), Cu (19.94 +/- 1.17 mu g/g) and Zn (42.53 +/- 3.08 mu g/g) were found in unwashed leaf samples taken from the roadside. However, the average lowest values of Cd (0.30 +/- 0.06 mu g/g) and Cu (5.99 +/- 0.21 mu g/g) were in washed leaf samples, whereas the lowest levels of Pb (1.19 +/- 0.12 mu g/g) and Zn (14.34 +/- 0.71 mu g/g) were in branches. In addition, there was also a direct correlation between heavy metal accumulation, traffic density and closeness to roadside. It was demonstrated that Celtis australis could be a useful plant species in the biomonitoring of environmental pollution with these four heavy metals. Moreover, the results also indicated that nettle tree barks might be employed in long-term measurements of heavy metal accumulation.
Keywords: Heavy metal pollution; European nettle tree; biomonitor; plant; bark; ECOLOGICAL CHARACTERISTICS; DISTRICT ISTANBUL; TRACE-ELEMENTS; BIOMONITOR; CONTAMINATION; INDUSTRIAL; STREET; PENDIK; LEAVES; WASTE